Analisa Kinerja Mesin Pengering Buah Pinang Tenaga Hibrid - Sepriyanto; Sigit Kurniawan; Sepdian (Jurnal INOVATOR, 2022)
The purpose of this study was to determine the performance of a hybrid dryer by combining the utilization of solar energy (solar dryer) and biomass power sources. Utilization of solar thermal energy sources by maximizing solar heat radiation sources which are absorbed directly into the drying chamber in the form of a transparent house with ventilation holes for fresh air to enter and moist air to exit. This process will produce hot air circulation (convection) in the drying chamber continuously so that the process of evaporation of water from the material being dried is faster. The temperature of the hybrid dryer with a sun source without the test material was 56º C. In the hybrid dryer test with a biomass combustion power source without the test material, the maximum temperature was 46 º C with a stable temperature of 40 º C. In the hybrid dryer test with a solar power source with the material test with a drying rate for 6 hours of drying there was a reduction in the mass of areca nut by 19%. The performance of the hybrid drying machine is better when the temperature is controlled with a setting temperature of 60º C. The average drying rate of areca nut from the hybrid dryer is 1 kg/hour